ANALISIS REALOKASI DAN REFOCUSING ANGGARAN DANA DESA PADA MASA PANDEMI COVID 19 (Studi Kasus Pada Desa Pancuran Gading, Kecamatan Tapung, Kabupaten Kampar) - Utami Juni Sania; Sari Nelly Ria; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to find out how to reallocate and refocus village funds for the preventionof Covid-19 in Pancuran Gading Village using William Dunn's 5 evaluation models, whatis the impact of reallocating and refocusing village funds for direct village cashassistance in Pancuran Gading Village and how the contribution of direct cashassistance funds for the prevention of Covid-19 in Pancuran Gading Village. In this studyusing qualitative methods with the type of case study. Data collection techniques usinginterview techniques, observation and documentation. To ensure the validity of the data,triangulation was carried out, namely source triangulation, technical triangulation andtime triangulation. Informants in this study were village heads, village secretaries, villagetreasurers, hamlet heads, community leaders and BLT recipients. Data analysis is doneby reducing data, presenting data and making conclusions. The results of this studyindicate that in terms of effectiveness, the budget refocusing policy has not been effectivein dealing with the Covid-19 pandemic outbreak. In terms of adequacy, the refocusing ofthe budgeted funds has not been sufficient in terms of various factors, especially the KUAPPAS which has been evaluated showing a deficit. In terms of equity, the reallocation ofthe budget through APBD refocusing has been carried out in stages with an evenallocation of the budget to all units of the COVID-19 task force as well as social netprovider programs. Viewed from responsiveness, the APBD budget refocusing programreceived several responses from the public, both positive and distorted responses, inwhich many people consider the Covid-19 budget to be used as a tool for budget politics.Judging from the accuracy, the use of funds that have been centralized through theunexpected expenditure budget has been maximized in order to achieve the desiredbudget reallocation target. For the contribution of BLT funds during the Covid-19pandemic, it does not provide financial guarantees for families, it's just that these fundscan help them with financial matters, both used for savings and for health. Keywords: Dana Desa, Realokasi, Refocusing, Covid-19